Organic Nitrates: Direct Antiplatelet Effects and Synergism with Prostacyclin - De Caterina, Raffaele; Giannessi, Daniela; Bernini, Walter; Mazzone, Annamaria (Thrombosis and Haemostasis, 1988)
Isosorbide dinitrate inhibits platelet function in vivo at concentrations about 10 times lower than in vitro (10-7 -10-6 vs. 10-6 -10-5 M). We investigated two possible reasons for this difference. Isosorbide dinitrate and its in vivo longer-lived metabolites, isosorbide-2- and isosorbide-5-mononitrate were incubated for 5 min with human platelet-rich plasma or washed platelets; irreversible aggregation was induced with threshold doses of ADP, adrenaline, collagen, arachidonic acid and thrombin, and thromboxane (TX) B2 production was measured by radioimmunoassay. Moreover, the concentration of exogenous prostacyclin required to inhibit platelet aggregation by 50% (IC50) after preincubation with isosorbide dinitrate or vehicle was determined. At 10-7 M, only isosorbide-2-mononitrate inhibited aggregation (-12%, p >0.05) and TX production (-36%, p >0.01) by ADP. At 10-6 M isosorbide-2-mononitrate inhibited aggregation by adrenaline more than the dinitrate (-41% vs. -25%, p >0.05). In addition, at supra-threshold doses of all the aggregating agents, isosorbide dinitrate decreased IC50 of prostacyclin from 2.7 ± 1.2 to 0.36 ± 0.2 nM. Generation of a platelet-active metabolite and synergism with prostacyclin are new properties of isosorbide dinitrate that may account for antiplatelet effects in vivo.
Keywords: Nitrates; Isosorbide dinitrate; Platelets; Prostacyclin